Risk Factors and Comorbidities Associated with Diabetic Kidney Disease - Satyajeet Roy; Olga Schweiker-Kahn; Behjath Jafry; Rachel Masel-Miller; Riya Sam Raju; Liam Martin Orta O'Neill; Caroline Rose Correia; Aditi Trivedi; Christopher Johnson; Christian Pilot; Jackson Saddemi; Aatqa Memon; et al. (SAGE Publishing, 2021)
Introduction/objectives: Diabetic Kidney Disease (DKD) is the leading cause of end-stage kidney disease. Despite optimal glycemic control and blood pressure management, progression to DKD cannot be halted in some patients. We aimed to find the association of modifiable and non-modifiable risk factors and comorbid conditions in patients with DKD. Methods: Retrospective medical record review of adult patients with diabetes mellitus (DM) was performed who visited our internal medicine office between January 1, 2020 and December 31, 2020. Results: Among 728 patients with DM, 471 (64.7%) patients had DKD, and 257 (35.3%) patients were without DKD. Among the group of patients with DKD, the majority were in CKD stage G1A2 (34.6%), followed equally by G2A2 and G3aA1 (16.8% each). Mean age of the patients with DKD was significantly greater than the patients without DKD (69.4 years vs 62.2 years; P  < .001). For each unit increase in age, there was a 7.8% increase in the odds of DKD (95% CI 5.3-10.4; P  < .001). Women had 2.32 times greater odds of DKD (95% CI, 1.41-3.81; P  = .001). We found decreased odds of DKD for those who consumed alcohol moderately (OR 0.612, 95% CI 0.377-0.994; P  < .05). Significantly higher frequencies of associations of several comorbid medical conditions were seen in patients with DKD compared to the patients without DKD, such as hypertension (91.9% vs 75.6%), hyperlipidemia (86.6% vs 78.2%), coronary artery disease (39.3% vs 16.8%), cerebrovascular accidents (13.4% vs 7.4%), congestive heart failure (12.9% vs 4.1%), carotid artery stenosis (11.3% vs 2.6%), aortic aneurysm (5.4% vs 2.0%), peripheral artery disease (10.8% vs 3.5%), gout (12.4% vs 5.5%), and osteoarthritis (41.4% vs 31.2%). Conclusions: In patients with diabetes, increasing age, female sex, and lack of moderate alcohol consumption were associated with increased odds of DKD. Higher frequencies of association of hypertension, hyperlipidemia, coronary artery disease, cerebrovascular accidents, congestive heart failure, carotid artery stenosis, aortic aneurysm, peripheral artery disease, gout, and osteoarthritis were also seen in patients with DKD.